Non-graded Education: Recognition of Individual Differences - Yuni Masrifatin (EDUCATIO : Journal of Education, 2018)
The objective of this research is to develop a non-graded education models in this model, the curriculum materials are adapted into sequentially arranged materials. Students are grouped on the bases of Reviews their ages, it is possible to have a variety of learning materials and a variety of learning activities within one classroom at the same time. An individual is mastery learning approach is implemented. The location of research was in the town of Surakarta. The initial activity was adapting the existing curriculum materials into sequential learning units. The non ~ graded model was tried out in grade 1 of SO Al Firdaus with 62 students (parallel classes). Research results indicate: i) The initial levels of competence of students in a classroom are heterogeneous. 2) In terms of language and sequence of materials, the adapted curriculum package was rated as excellent, but in appropriateness to the levels of development, a few materials for the lower grades need to be revised. 3) Teachers and parents Agreed on the heterogeneity of classes in schools, but disagreed on the feasibility of multilevel curriculum materials and multi-modality of learning. The two groups Also Agreed on the low competence of teachers in teaching non-graded classrooms. 4) After one year in progress, the non-graded models Showed beneficial for fast and slow learners